The brothers Hawthorne - Barnes, Jennifer Lynn (2023)
"Grayson Hawthorne was raised as the heir apparent to his billionaire grandfather, taught from the cradle to put family first. Now the great Tobias Hawthorne is dead and his family disinherited, but some lessons linger. When Grayson's half-sisters find themselves in trouble, he swoops in to do what he does best: take care of the problem--efficiently, effectively, mercilessly. And without getting bogged down in emotional entanglements. Jameson Hawthorne is a risk-taker, a sensation-seeker, a player of games. When his mysterious father appears and asks for a favor, Jameson can't resist the challenge. Now he must infiltrate London's most exclusive underground gambling club, which caters to the rich, the powerful, and the aristocratic, and win an impossible game of greatest stakes. Luckily, Jameson Hawthorne lives for impossible. Drawn into twisted games on opposite sides of the globe, Grayson and Jameson--with the help of their brothers and the girl who inherited their grandfather's fortune--must dig deep to decide who they want to be and what each of them will sacrifice to win" --
Sequel to: The final gambit.
Ages 12 and Up.
Keywords: Brothers -- Juvenile fiction; Wealth -- Juvenile fiction; Inheritance and succession -- Juvenile fiction; Family secrets -- Juvenile fiction; Rich people -- Juvenile fiction; Puzzles -- Juvenile fiction; Brothers -- Fiction; Inheritance and succession -- Fiction; Wealth -- Fiction; Puzzles -- Fiction; Young adult fiction; Detective and mystery fiction; Novels